Uncommitted Couples: Some Efficiency and Policy Implications of Marital Bargaining - Saku Aura (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper studies a married couple's dynamic investment and consumption choices under the assumption that the couple cannot commit across time not to renegotiate their decisions. The inefficiencies that can arise are characterized. Efficiency properties of different divorce asset-division regimes are examined. A stylized common-law regime is shown to lead to fully efficient outcome in a simple model while it is shown that under a community-property regime the couple is unlikely to attain full efficiency. The effect of the inability to commit across time on the savings level is examined under a tractable special case of the model.
Keywords: 330